Contrastive Observations on Possessive and Pseudo-possessive Constructions in Spanish and Italian (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
Linguistic possession has been studied in various ways from all linguistic viewpoints, from the pioneering works of Lévy-Bruhl (1914) to those in generative grammar by Velázquez (1996), in linguistic typology by Hagège (1978) and Koptjevskaja-Tamm (2002) or in cognitive grammar by Nikiforidou (1991), Heine (1997) and Pamies (2001; 2004). However, many doubts remain on that question. There is a surprisingly high cross-linguistic variation in the relation between meaning (the concept of possession) and grammatical forms (possessive and genitive constructions, prepositions, possession verbs, etc.), even within the same historical family, and there are frequent contradictions which could be explained in a simple way by applying the concept of grammatical metaphor (Halliday 1985) and taking into account contextual issues.Key words: possession, possessive constructions, dative constructions, contrastive grammar, grammatical metaphor.